Siswa Smart Berinvestasi: Strategi Meningkatkan Inklusi Pasar Modal di Kalangan Siswa/i SMA Global Mandiri Bekasi dan SMA Santo Josef Pangkalpinang - Yupiter Gulo (Indonesia Berdaya, 2023)
The interest of the millennial generation and generation Z to invest in the capital market has increased significantly, especially during and after the impact of the Covid-19 pandemic hit the world. In addition to increasing awareness of investing among the public, it is also due to the capital market inclusion program which provides easy service to the whole community. This must be followed by literacy – capital market education among high school students so that they are not trapped in fraudulent investment practices that take many victims. Smart Invest Students, is one of the strategies to increase capital market inclusion among high school students, as has been done by P3M TSM Jakarta for the last few years. Abstrak: Minat generasi milenial dan generasi Z untuk berinvestasi di pasar modal meningkat dengan signifikan, terutama selama dan sesudah hantaman pandemi covid-19 melanda dunia. Selain meningkatnya kesadaran berinvestasi dikalangan masyarakat, juga karena program inkluasi pasar modal yang memberikan kemudahan layanan ke seluruh masyarakat. Hal ini harus diikuti dengan literasi – edukasi pasar modal di kalangan siswa SMA agar tidak terjebak pada praktek investasi bodong yang banyak memakan korban. Siswa Smart Berinvestasi, menjadi salah satu strategi untuk meningkatkan inklusi pasar modal di kalangan siswa SMA, seperti yang sudah dikerjakan oleh P3M TSM Jakarta selama beberapa tahun terakhir.